Pendampingan Metode 4T 1 IM (Tasmi’, Tilawah, Tafhim, Tikrar dan Murojaah) Untuk Peningkatan Hafalan Al-Qurán Santri TPA Jannatul Firdaus Siman Ponorogo - Septrianto, Wahyu; Zubaidi, Sujiat; Anggara, Deki Ridho Adi; Firdaus, Muhammad Irkham; Muhammad, Emyr; Sasongko, Yogi Banar (Journal Of Human And Education (JAHE), 2025)
Increasing memorization of the Al-Qur'an among children is an important step in forming a generation with noble morals and a deep understanding of religion. TPA Jannatul Firdaus Siman, located in Siman District, Ponorogo, applies the Ummi method to teach the Koran effectively. However, the problems faced by this TPA are related to the students' difficulty in memorizing Juz 30, which is caused by various factors, including limited time, lack of innovative strategies, and lack of motivation from the surrounding environment. This article explains the importance of mentoring in implementing the 4T 1M method to improve students' memorization abilities. Through the application of the Tasmi', Tilawah, Tafhim, Tikrar, and Murajaah methods, it is hoped that students can memorize the Al-Qur'an better and understand its content. Keywords: Memorizing the Qur'an, 4T 1M Method, TPA Al-Qur'an Education